ANALISA DAN PERANCANGAN SISTEM INFORMASI NILAI SISWA BERBASIS WEB PADA MTs ROUDHOTUL MUHAAJIRIN - Maulida Shyfa Mahadewi (2023)
The process of inputting student scores at MTs Roudhotul Muhaajirin still uses the manual method. This method is the main factor for data input errors, including calculating wrong values, if any data is input incorrectly it must be changed one by one, and also errors when placing data. Therefore, the author designed a website-based application called "Sistem Informasi Nilai Siswa" to solve this problem. In making the system, the author uses the Waterfall method and uses the CodeIgniter Framework with PHP language.